Strathcona Street - Athabasca Landing, AB - (Author); (Interviewer); (Publisher) (1912)
Photograph - Three men standing in front of the Hudson's Bay Company building, Athabasca, Alberta. The Imperial Bank, Government Telegraph, and Revillon Freres buildings are also visible